The Effect of Leadership and Motivation on Organizational Commitment at PT. Indo Perkasa Indonesia in Tangerang - Eka, Priehadi Dhasa (Universitas Negeri Makassar, 2018)
Leadership plays an important role because leaders will move different subordinates. The purpose of this study was to determine the effect of leadership and motivation on organizational commitment at PT. Indo Perkasa Indonesia in Tangerang. The method used in this research is descriptive with an associative approach, the sampling technique used is proportional random sampling using the census or saturated sampling method with a sample of 80 respondents. The analysis tool uses instrument testing, classical assumption testing, regression testing, determination coefficient testing and hypothesis testing. The results of the study concluded that there is a positive and significant influence both partially and simultaneously between leadership and motivation on organizational commitment with a contribution of 0.503 or 50.3% while the remaining 49.7% is influenced by other factors. Hypothesis testing obtained Fcount> Ftable (38,975> 2,720) thus H0 is rejected and H3 is accepted meaning that there is a positive and significant effect simultaneously between leadership and motivation on organizational commitment at PT. Indo Perkasa Indonesia in Tangerang.